Structure‐based pharmacophore modeling, virtual screening approaches to identifying the potent hepatitis C viral protease and polymerase novel inhibitors. Issue 8 (20th June 2022) - Venkatesan, Arthi; Dhanabalan, Anantha Krishnan; Rajendran, Selvakumar; Shanmugasundharam, Shyamala Gowri; Gunasekaran, Krishnasamy; Febin Prabhu Dass, J.
Abstract: Hepatitis C is an infectious disease that leads to acute and chronic liver illnesses. Currently, there are no effective vaccines against this deadly virus. Direct acting antiviral (DAA) drugs are given in the combination with ribavirin and pegylated interferon which lead to adverse effects. Through in silico analysis, the structure‐based docking study was performed against NS3/4A protease and NS5B polymerase proteins of HCV. In the current study, multiple e‐pharmacophore‐based virtual screening methods such as HTVS, SP, and XP were carried out to screen natural compounds and enamine databases. Our result outcomes revealed that CID AE‐848/13196185 and CID AE‐848/36959205 compounds show good binding interactions with protease protein. In addition, CID 15081408 and CID 173568 show better binding interactions with the polymerase protein. Further to validate the docking results, we performed molecular dynamics simulation for the top hit compounds bound with protease and polymerase proteins to illustrate conformational differences in the stability compared with the active site of the cocrystal inhibitor. Thus, the current study emphasizes these compounds could be an effective drug to treat HCV.